Pronominal This: Deictic of Commitment - Boldog, Gyöngyi (Working Papers in Language Pedagogy, 2009)
This paper shows that a particular utterance examined in its discourse context operates on multiple linguistic levels. On syntactic level, the utterance which contains the ascriptive formula ‘This is a(n)+ Adj+N’ with the subject this referring to a human can be analyzed in terms of congruity between its reference formulation and the local syntactic norm of the discourse. On the semantic level, the same utterance can be read as a sequence functioning as an assessment. Finally, on interactional level, the utterance is recognized as an act of the speaker’s commitment to their own words.